Multimedialne rozwiązania w działaniach terapeutycznych = Multimedia solutions in therapeutic activities - Nowicka, Ewa; Banasiak-Macherska, Ewa (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this article is to present the importance of information and communication technologies in therapeutic and speech therapy activities. The authors focus on the issues related to the implementation of the main principles of the therapeutic process involving media and multimedia. The multimedia suggestions mentioned are a perfect addition to traditional therapeutic methods. Taking into account the individual needs and abilities of students participating in both pedagogical and speech therapy classes, multimedia contribute to making widely understood therapeutic interventions at school more attractive.
Keywords: media; multimedia; pedagogical therapy; speech therapy; terapia pedagogiczna; logopedia